Sinosenecio lichuanensis (Asteraceae, Senecioneae), a new species from Hubei, China - Jin, Zi-Chao; Du, Si-Yi; Yi, Yong-Mei; Chen, You-Sheng (Phytotaxa, 2025)
Sinosenecio lichuanensis (Asteraceae, Senecioneae), a new species from Lichuan County, Enshi Tujia and Miao Autonomous Prefecture, Hubei Province, China, is described and illustrated here. This new species is readily distinguishable from all its congeners by a combination of morphological characters, including the presence of stolons, basal and lower cauline leaves with winged petioles, and leaf blades that are cordate to ovate and pinnately veined. Phylogenetic analyses based on ITS sequence data further corroborate the placement of S. lichuanensis within Sinosenecio.